2015
DOI: 10.1371/journal.pntd.0003683
|View full text |Cite
|
Sign up to set email alerts
|

Down Regulation of NO Signaling in Trypanosoma cruzi upon Parasite-Extracellular Matrix Interaction: Changes in Protein Modification by Nitrosylation and Nitration

Abstract: BackgroundAdhesion of the Trypanosoma cruzi trypomastigotes, the causative agent of Chagas' disease in humans, to components of the extracellular matrix (ECM) is an important step in host cell invasion. The signaling events triggered in the parasite upon binding to ECM are less explored and, to our knowledge, there is no data available regarding •NO signaling.Methodology/Principal FindingsTrypomastigotes were incubated with ECM for different periods of time. Nitrated and S-nitrosylated proteins were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Alternatively, selfprotein oxidative modifications could be exploited by the parasite for signaling various pathways. Indeed, it was shown that in presence of extracellular matrix that constitute the cell surrounding layer crossed by the parasite for invasion of host cells, pathogen undergoes selective S-nitrosylation and tyrosine nitration (Pereira et al, 2015). These authors proposed that T. cruzi actively modulates its nitrosylation allowing its internalization into host cells.…”
Section: The Complexity Of Ros and Rns Cytotoxic Effects On T Cruzimentioning
confidence: 99%
“…Alternatively, selfprotein oxidative modifications could be exploited by the parasite for signaling various pathways. Indeed, it was shown that in presence of extracellular matrix that constitute the cell surrounding layer crossed by the parasite for invasion of host cells, pathogen undergoes selective S-nitrosylation and tyrosine nitration (Pereira et al, 2015). These authors proposed that T. cruzi actively modulates its nitrosylation allowing its internalization into host cells.…”
Section: The Complexity Of Ros and Rns Cytotoxic Effects On T Cruzimentioning
confidence: 99%
“…Protein S‐nitrosylation involves the addition of a NO to cysteine thiols and regulates diverse cellular functions and signaling events including phosphorylation, acetylation, ubiquitylation and redox‐based cellular signaling . In T. cruzi , this PTM has been mapped by nLC‐MS/MS based detection of S‐nitrosylated peptides including enolase and histones after incubation of trypomastigotes with extracellular matrix . Currently, no MS‐based studies on Leishmania have mapped protein S‐nitrosylation of the parasites in different physiological and stress conditions.…”
Section: Proteomics Approaches In Leishmaniamentioning
confidence: 99%
“…nitrate and nitrite. Recent pro les of S-nitrosylated and nitrated proteomes in protists showed that glycolytic enzymes and ribosomal proteins are the general targets for SNO modi cation [18][19][20][21]. It has been reported that protein nitrosylation enhances the activity of glycolytic enzymes in mice [22].…”
Section: Introductionmentioning
confidence: 99%